Factors Influencing the Occurrence of Pulmonary Tuberculosis in the Productive Age Group - Anisa Nanang Sulistiyowati; Ardiansa Ardiansa; Umratun Hayati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Tuberculosis (TB) remains a major public health issue, particularly in developing countries like Indonesia, which ranks third globally for TB cases. In Papua, the number of TB cases has been steadily increasing, especially among the productive age group (15-50 years). This study aims to analyze the factors influencing the occurrence of pulmonary tuberculosis in Nabire District, Central Papua, using an observational analytic design with a case-control study. The case population in this study consists of all patients diagnosed with pulmonary tuberculosis (TB) BTA (+) residing in the working area of Sriwini Health Center, totaling 50 individuals. The control population includes patients diagnosed with negative pulmonary TB, totaling 100 individuals, with a total sample size of 150, selected using the total sampling technique. The instrument used in this study is a questionnaire, which contains a list of questions related to the respondent's identity and the variables of the study, including age, gender, occupation, smoking status, alcohol consumption, housing density, house lighting, and household contact history. The questionnaire used is standardized with a Cronbach's alpha value of 0.937, so no validity or reliability testing was conducted. The data from this study were analyzed using the chi-square test. The results provide valuable insights into the local epidemiology of TB and underscore the need for targeted public health interventions to address these risk factors. Improving TB detection, treatment adherence, and public awareness are essential for controlling the TB burden in Nabire and similar areas in Central Papua.